1996
DOI: 10.1099/00222615-45-2-149
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus in bronchoalveolar lavage specimens from patients with AIDS: comparison with antigenaemia and viraemia

Abstract: Pulmonary infection with cytomegalovirus (CMV) is a well recognised complication of AIDS. It is often possible to detect CMV-infected cells in bronchoalveolar lavage (BAL) specimens with monoclonal antibodies, but the clinical significance of their presence remains unclear. To investigate this, 24 AIDS patients were tested for CMV antigenaemia and viraemia, in addition to CMV detection in BAL. CMV was detected in the BAL of nine patients (38%), five with clinical and laboratory evidence of pulmonary infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that 28–69% of HIV-infected patients also exhibit co-infection with P. jirovecii andCMV [710]. However, CMV can also be found in the respiratory secretions of patients without clear signs of pneumonia [11], and the pathogenesis and prognosis of pulmonary CMV infection with PJP in non-HIV patients is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that 28–69% of HIV-infected patients also exhibit co-infection with P. jirovecii andCMV [710]. However, CMV can also be found in the respiratory secretions of patients without clear signs of pneumonia [11], and the pathogenesis and prognosis of pulmonary CMV infection with PJP in non-HIV patients is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Blood antigenemia methods (3 studies [94][95][96]: N = 91) had an integrated sensitivity of 0.67 (95% CI: 0.54-0.79) and integrated specificity of 0.87 (95% CI: 0.73-0.95) when the definition of "positive" was at least one positive cell per 200,000. Furthermore, the frequency of adverse events with BAL was as follows: mortality, 0.000% (95% CI: 0.000-0.035).…”
Section: Summary Of Evidencementioning
confidence: 99%